The Kingdom of God and Political Engagement in Nigeria: Exploring the Intersection of Faith and Politics - Jezreel Smith Mietuade (International Journal of Religion, Humanity and Cultural Heritage, 2025)
The tension between Christian discipleship and political engagement has been a long-standing issue, especially in Nigeria, where corruption, inequality, and poor governance remain serious challenges. This study explores the Kingdom of God and political engagement in Nigeria, asking whether faithful discipleship allows Christians to participate in politics or whether politics risks corrupting their faith. This study aims to examine Jesus’ teachings on the Kingdom of God and show how they apply to Christian involvement in Nigerian politics today. Employing biblical exegesis, theological reflection, and contextual application, the study considers the words of Jesus about God’s Kingdom and applies them to Nigeria’s political realities. The research shows that the Kingdom of God is not limited to private spirituality but represents God’s rule that calls for justice, humility, and service. It challenges corruption, exposes oppression, and redefines leadership as service to others. Christians are therefore called to reflect Kingdom values in public life. Findings reveal that the Kingdom shapes Christian political ethics in Nigeria by stressing fairness for the poor, honesty in leadership, and peace in society. This means Christians should not withdraw from politics but engage in it with values rooted in Christ. The significance of this study is that it helps the Church see politics in Nigeria as an opportunity to witness to God’s reign in a society marked by selfishness and corruption. The study concludes that faithful discipleship includes responsible political participation and recommends that churches prepare members to engage politics with integrity, justice, and compassion.